Economy-wide climate change impacts on green water droughts based on the hydrologic simulations. (May 2019) - Kang, Hyunwoo; Sridhar, Venkataramana; Mills, Bradford F.; Hession, W. Cully; Ogejo, Jactone A.
Abstract: The impacts of climate change on green water drought and associated economic activity can be simulated with future climate projections, hydrologic models that predict drought indices based on reliable soil moisture, and historic relationships between drought indices and agricultural sector impacts. This study compares the potential impacts of climate change on future agricultural drought and economic conditions in a rural and an urban congressional district in Northern Virginia (VA). The Variable Infiltration Capacity (VIC) model is applied to estimate a soil moisture index (SSI), which is then employed with historic and future climate data to generate SSI predictions. Economic impacts of future SSI changes are inferred from linear regression analysis of the historic relationship between annual mean SSI values and agricultural production values for a seven-year period (2010–2016). The two districts face similar future temperature and precipitation changes due to geographic proximity, but soil moisture, agricultural production and economy-wide responses to climate change differ considerably due to differences in land use and economic structure. In the more rural district, the mean value of drought occurrence increases 38%, while in the more urban district the increase is only 15%. Similarly, economy-wide agricultural sector value added decreases between 17% and 22% in the rural district and between 1 and 5% in the urban district. More studies are required to understand the impacts of adaption on agricultural and other economic sectors both rural and urban regions. More research should be carried out with an application of blue water droughts that have significant impacts to explain the economic impact of droughts. Graphical abstract: Unlabelled Image Highlights: Impacts of climate change using coupled soil moisture and economic model. Future drought occurrence increased over the study region. Impacts of agriculture and economy differ due to land use and economic structure. Agricultural sector value decreased 17–22% in rural and 1–5% in urban areas.